FISH FARMING WASTE UTILIZATON FOR INCREASING SLUDGE WORM (Tubifex sp.) BIOMASS GROWTH - Ardana, Putu Pande Nico; Abidin, Zaenal; Diniarti, Nanda (Jurnal Perikanan Unram, 2018)
The aims of the research were to evaluate the biomass growth of sludge worms (Tubifex sp.) which were cultivated by using waste from fish rearing and to calculate the ability of sludge worm to reduce total organic matter (TOM). The worms were cultivated in private fish rearing facility in Sokong, District of Tanjung, North Lombok, West Nusa Tenggara. The experiment was conducted by using Completely Randomized Design. The wastes, which were tested, were feces of catfish, carp, and tilapia with three replications. The result showed that biomass of sludge worms cultivating in catfish waste media reached the peak on the 45th day, while in carp and tilapia waste media, the biomass peaks were resulted on the 60th day. The highest biomass of sludge worms was obtained from cultivation in catfish waste media by 712,7 g/m2. In addtion, the sludge worms had ability to reduce TOM and NH3 in water. It was proved by the reduction of TOM and NH3 concentration in the water used in rearing the worms.